Spiritual Well-being in Cancer Patients who Undergo Chemotherapy - M Rezaei; N Seyedfatemi; F Hosseini (Tehran University of Medical Sciences, 2008)
Background & Aim: Spiritual well-being harmonizes several dimensions of human's life and is essential for coping with diseases. Chronic illnesses such as cancer cause crisis in physical, psychological, and spiritual dimensions of ones life. This study aimed to measure the spiritual well-being in cancer patients who undergo chemotherapy. Methods & Materials: In this cross-sectional, descriptive-correlational study, Paloutzian & Ellison's Spiritual Well-being Self-report questionnaire was completed by 360 cancer patients. Patients were recruited using sequential sampling method. The inclusion criteria were being more than 20 years old, and being able to read and write. Data were analyzed using chi-square and Pearson tests in SPSS (version 11). Results: The study findings revealed that the mean scores for spiritual well-being, religious well-being, and existential well-being were (98.35±14.36), (54.67±5.92), (43.67±10.01), respectively. Also, statistically significant relations were found between age, marital status, and educational levels with spiritual well-being (P<0.001). Conclusion: Findings showed that the level of spiritual well-being was high in cancer patients. Moreover, as it is expected in Iranian culture, the level of religious well-being was more than existential well-being. There were significant relationships between spiritual well-being and personal characteristics. Hence, nurses should consider personal characteristics in their caring programs and choose a comprehensive and holistic approach toward their patients' care.   Key words: cancer, chemotherapy, spiritual well-being